Struktura pravosodnega sistema na Štajerskem v 15., 16. in 17. stoletju - Holcman, Borut (Arhivi, 1997)
In his article the author deals with the structure of the judicial system in Styria, and due to the specific characteristics of the period, gives an outline of the circumstances which also strongly influenced the structure. In addition to giving an overview of the judicial system, the article also contains fragments of insight into the workings of the judicial administration and the criminal judicial system. At the end of his article, the author lists the sources and literature on the subject matter.
Keywords: pravosodni sistemi; 15./17.st.; zgodovinski pregledi; Styria; Štajerska